2021
DOI: 10.1029/2020gl090769
|View full text |Cite
|
Sign up to set email alerts
|

Helium and Argon Partitioning Between Liquid Iron and Silicate Melt at High Pressure

Abstract: Whether Earth’s core is a significant repository of noble gases is an open question because their partitioning between liquid metal and silicate melt during core formation is poorly known. Here we calculated the He and Ar partition coefficients (D) between liquid Fe and MgSiO3 melt from 20 to 135 GPa at 5,000 K using ab initio molecular dynamics combined with thermodynamic integration. Our simulations show that DHe does not change significantly with pressure, while DAr increases strongly with increasing pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Therefore the variation of Dnormalm/normals in Figure 2a is mainly controlled by T rather than P . A recent computational study (Xiong et al., 2021) also suggested a negligible P effect on Dnormalm/normals. The T effect can be seen in Figure 2b: Dnormalm/normals increases approximately by three orders of magnitude from 3,000 to 5,000 K for all metallic compositions of this study.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Therefore the variation of Dnormalm/normals in Figure 2a is mainly controlled by T rather than P . A recent computational study (Xiong et al., 2021) also suggested a negligible P effect on Dnormalm/normals. The T effect can be seen in Figure 2b: Dnormalm/normals increases approximately by three orders of magnitude from 3,000 to 5,000 K for all metallic compositions of this study.…”
Section: Resultssupporting
confidence: 74%
“…The T effect can be seen in Figure 2b: m /s E D increases approximately by three orders of magnitude from 3000 to 5000 K for all metallic compositions of this study. A similar T effect was also reported in a previous DFT-MD study (Xiong et al, 2018) which has shown potassium iron-silicate partition coefficient varies by three orders of magnitude from 3000 to 5000 K. Given the strong T effect and that the P-T conditions in our study follow the temperature profile of a magma ocean (Figure S1), our results may be more relevant to represent metal-silicate fractionation of He during planetary accretion and differentiation than the results of DFT-MD simulations from Xiong et al (2021) at 5000 K and experiments from Bouhifd, Jephcoat, et al (2013) over a limited P and T range.…”
Section: Partition Coefficientssupporting
confidence: 83%
See 3 more Smart Citations